Pengukuran Lingkar Lengan Atas pada Wanita Usia Subur di Kabupaten Jayawijaya: Mid-Upper Arm Circumference Measurement among Adult Women in Jayawijaya Regency - Fatiah, Mona Safitri; Pamangin, Lisda Oktavia Madu; Tambing, Yane; Izaac, Fransina Alfonsina (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Measurement of Upper Arm Circumference (MUAC) is one form of an indicator used to assess the status of Chronic Energy Deficiency (CED) in pregnant and adult women. The purpose of the Community Engagement Program (CEP) is to conduct nutritional status screening on Women of Reproductive Age (WRA) through MUAC measurement in Jayawijaya Regency. The CEP was conducted in Napua District, Jayawijaya Regency, in October 2022, targeting 110 WRA aged between 15 and 49 years. The activities were carried out through data collection, community education, and the practice of MUAC measurement on WRA. The results of this program found that approximately 71% of WRA had MUAC measurements greater than 23.5 cm, and there was an increase of about 18.1% in knowledge about CED. Additionally, there was a 24.5% increase in WRA's knowledge in conducting MUAC measurements before and after the intervention. The screening also identified a small percentage of WRA with nutritional status below 23.5 cm. The education and practice of MUAC measurement were found to have a significant impact on increasing WRA's knowledge. Therefore, the CEP recommends periodic education provided by nutrition experts during every integrated health post activity and conducting door-to-door visits for pregnant women with CED. Furthermore, there is a need for an increase in the provision of Supplementary Food (SF) such as biscuits and local food.